A ASSISTANCE IN PROMOTIONAL DESIGN CREATION FOR SMEs PAPINE MAS WIRO KADIPIRO DISTRICT, SURAKARTA - Lukitasari, Evelyne Henny; Haryanto, Eko Sri; Heriwati, Hesti (LPPM Universitas Al Muslim, 2024)
This Community-Based Empowerment Scheme community service program seeks to empower MSME groups in Kadipiro Village, Banjarsari District, Surakarta City. The partner of this activity is the PAPINE MAS WIRO MSME Group which engaged in culinary sector, both food and snacks. When it was first established, this group received an enthusiastic response from MSME members and residents. However, its development has declined, so the partner hopes that with this activity the Papine Mas Wiro MSME Group will get a better income. Efforts that were made including design and social media utilization for promotion, online sales as an alternative, designing good packaging, and designing attractive booths to attract visitors in making purchases. The methods used in community service activities are lectures, discussions, training, monitoring, and partner mentoring. Training included creating visual promotional content, creating product promotional videos, and online sales training through the marketplace, as well as copywriter training. The benefits obtained by partners are increased skills, increasing sales turnover and improving the partner's economy. From the implementation of this activity, it was found that: 1) a social media to market Papine Mas Wiro MSME products was established as a means of introducing and marketing products from these MSME actors, and 2) Papine Mas Wiro MSME actors aware of the importance of attractive designs to be uploaded on social media.